ADHESIVE FILM FOR METAL TERMINAL, METAL TERMINAL WITH ADHESIVE FILM FOR METAL TERMINAL, ELECTRICITY STORAGE DEVICE USING ADHESIVE FILM FOR METAL TERMINAL, AND METHOD FOR MANUFACTURING ELECTRICITY STORAGE DEVICE

The adhesive film for metal terminals, composed of specific polyolefin layers, addresses the issue of reduced adhesion at low bonding temperatures by maintaining high adhesion strength, thereby improving the sealing performance of electricity storage devices.

JP7600941B2Active Publication Date: 2024-12-17DAI NIPPON PRINTING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021154717
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-10
Filing Date
2021-09-22
Publication Date
2024-12-17
Estimated Expiration
2040-07-10

AI Technical Summary

Technical Problem

Conventional adhesive films for metal terminals in electricity storage devices exhibit decreased adhesion strength when bonded at lower temperatures (140°C to 180°C), leading to insufficient bonding between metal terminals and exterior materials.

Method used

An adhesive film for metal terminals with a specific tensile modulus after heating that is lower than before heating, ensuring high adhesion strength even at low bonding temperatures, composed of layers such as acid-modified polypropylene and polypropylene, interposed between the metal terminal and exterior material.

Benefits of technology

The adhesive film maintains high adhesion strength to metal terminals at low bonding temperatures, enhancing the sealing performance of electricity storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600941000004
    Figure 0007600941000004
  • Figure 0007600941000005
    Figure 0007600941000005
  • Figure 0007600941000006
    Figure 0007600941000006
Patent Text Reader

Abstract

To provide an adhesive film for metal terminal which presents a high adhesion strength with respect to a metal terminal even in a case where a heating temperature in the case of adhesion to the metal terminal is a low temperature ranging e.g., from 140°C to 180°C.SOLUTION: The present invention relates to an adhesive film for a metal terminal interposed between the metal terminal which is electrically connected to an electrode of a power storage device element, and a sheath material for power storage device encapsulating the power storage device element. In the adhesive film for the metal terminal, a value of a tensile modulus A of elasticity after heating is smaller than a value of a tensile modulus B of elasticity before heating, where the tensile modulus A of elasticity after heating is a tensile modulus of elasticity which is measured in an environment at 25°C after settling for 12 seconds in a heating temperature at 140°C and further settling for one hour in an environment at 25°C, and the tensile modulus B of elasticity before heating is a tensile modulus of elasticity which is measured in the environment at 25°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an adhesive film for metal terminals, a metal terminal with an adhesive film for metal terminals, an electricity storage device using the adhesive film for metal terminals, and a method for manufacturing an electricity storage device. [Background technology]

[0002] Conventionally, various types of electricity storage devices have been developed, and in all electricity storage devices, exterior materials for electricity storage devices are essential components for sealing electricity storage device elements such as electrodes and electrolytes. Conventionally, metal exterior materials for electricity storage devices have been widely used as exterior materials for electricity storage devices, but in recent years, with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., electricity storage devices are required to have a variety of shapes and are required to be thin and lightweight. However, conventionally widely used metal exterior materials for electricity storage devices have the disadvantages that it is difficult to keep up with the diversification of shapes and there is also a limit to the weight reduction.

[0003] In recent years, a laminated sheet in which a base layer / adhesive layer / barrier layer / thermal adhesive resin layer are laminated in this order has been proposed as an exterior material for an electricity storage device that can be easily processed into various shapes and can be made thinner and lighter. When such a film-like exterior material for an electricity storage device is used, the periphery of the exterior material for an electricity storage device is heat-sealed and thermally fused with heat sealing in a state in which the thermal adhesive resin layers positioned in the innermost layers of the exterior material for an electricity storage device face each other, thereby sealing the electricity storage device element with the exterior material for an electricity storage device.

[0004] A metal terminal protrudes from the heat-sealed portion of the exterior material for an electricity storage device, and the electricity storage device element sealed with the exterior material for an electricity storage device is electrically connected to the outside by the metal terminal electrically connected to the electrode of the electricity storage device element. That is, among the heat-sealed portions of the exterior material for an electricity storage device, the portion where the metal terminal is present is heat-sealed in a state where the metal terminal is sandwiched between the heat-sealable resin layer. Since the metal terminal and the heat-sealable resin layer are made of different materials, adhesion is likely to decrease at the interface between the metal terminal and the heat-sealable resin layer.

[0005] For this reason, an adhesive film is sometimes disposed between the metal terminal and the heat-sealable resin layer for the purpose of improving the adhesion therebetween. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2015-79638 A Summary of the Invention [Problem to be solved by the invention]

[0007] Such adhesive films are required to have high adhesion to exterior packaging materials for electricity storage devices and to metal terminals.

[0008] In the process of bonding a metal terminal and an exterior material for a power storage device via an adhesive film, it may be necessary to perform bonding by heating at a low temperature, for example, 140°C to 180°C. Conventionally, the heating temperature in the bonding process is generally about 190°C, and when the heating temperature during bonding is lower than conventionally, the adhesive strength of the adhesive film to the metal terminal tends to decrease. Depending on the degree of decrease in adhesive strength, the adhesive strength between the exterior material for a power storage device and the metal terminal via the adhesive film becomes insufficient.

[0009] Under these circumstances, the main object of the present disclosure is to provide an adhesive film for metal terminals that exhibits high adhesive strength to metal terminals even when the heating temperature when adhered to the metal terminal is low, for example, from 140° C. to 180° C. Furthermore, the present disclosure also aims to provide a metal terminal with an adhesive film for metal terminals, an electricity storage device using the adhesive film for metal terminals, and a method for manufacturing the electricity storage device. [Means for solving the problem]

[0010] The inventors of the present disclosure conducted intensive research to solve the above problems. As a result, they found that an adhesive film for a metal terminal in which the tensile modulus after heating at a temperature of 140° C. is smaller than the tensile modulus B before heating exhibits high adhesive strength to the metal terminal even when the heating temperature when adhering to the metal terminal is low, for example, from 140° C. to 180° C. The present disclosure was completed through further research based on such findings.

[0011] That is, the present disclosure provides the inventions of the following aspects. An adhesive film for a metal terminal, which is interposed between a metal terminal electrically connected to an electrode of an electricity storage device element and an exterior material for an electricity storage device that encapsulates the electricity storage device element, The adhesive film for a metal terminal has a tensile modulus A value after heating described below that is smaller than a tensile modulus B value before heating described below. Tensile modulus A after heating: The tensile modulus measured in an environment at a temperature of 25°C after leaving the sample to stand for 12 seconds in a heated environment at a temperature of 140°C and then leaving the sample to stand for one hour in an environment at a temperature of 25°C. Tensile modulus B before heating: Tensile modulus measured in an environment at a temperature of 25°C. Effect of the Invention

[0012] According to the present disclosure, it is possible to provide an adhesive film for metal terminals that exhibits high adhesive strength to metal terminals even when the heating temperature when adhering to the metal terminal is low, for example, from 140° C. to 180° C. Furthermore, according to the present disclosure, it is also possible to provide a metal terminal with the adhesive film for metal terminals, an electricity storage device using the adhesive film for metal terminals, and a method for manufacturing an electricity storage device. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic plan view of the electricity storage device of the present disclosure. [Diagram 2] 2 is a schematic cross-sectional view taken along line AA' in FIG. 1. [Diagram 3] 2 is a schematic cross-sectional view taken along line BB' in FIG. 1. [Figure 4] 1 is a schematic cross-sectional view of an adhesive film for metal terminals according to the present disclosure. [Diagram 5] 1 is a schematic cross-sectional view of an adhesive film for metal terminals according to the present disclosure. [Figure 6] 1 is a schematic cross-sectional view of an adhesive film for metal terminals according to the present disclosure. [Figure 7] 1 is a schematic cross-sectional view of an adhesive film for metal terminals according to the present disclosure. [Figure 8] 1 is a schematic cross-sectional view of an exterior material for an electricity storage device according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The adhesive film for a metal terminal of the present disclosure is an adhesive film for a metal terminal interposed between a metal terminal electrically connected to an electrode of an electricity storage device element and an exterior material for an electricity storage device that seals the electricity storage device element. The adhesive film for a metal terminal of the present disclosure is characterized in that the value of tensile modulus A after heating described below is smaller than the value of tensile modulus B before heating described below. Tensile modulus A after heating: the tensile modulus measured in an environment at a temperature of 25°C after leaving the sample to stand for 12 seconds in a heated environment at a temperature of 140°C and then leaving the sample to stand for one hour in an environment at a temperature of 25°C. Tensile modulus B before heating: Tensile modulus measured in an environment at a temperature of 25°C.

[0015] The adhesive film for metal terminal of the present disclosure can exhibit high adhesive strength to metal terminals even when heated to a low temperature of, for example, 140°C to 180°C when adhered to the metal terminal.

[0016] The electric storage device of the present disclosure is an electric storage device including at least an electric storage device element having a positive electrode, a negative electrode, and an electrolyte, an exterior material for an electric storage device that seals the electric storage device element, and metal terminals electrically connected to the positive electrode and the negative electrode, respectively, and protruding outside the exterior material for an electric storage device, and is characterized in that the adhesive film for a metal terminal of the present disclosure is interposed between the metal terminal and the exterior material for an electric storage device. The adhesive film for a metal terminal of the present disclosure, an electric storage device using the adhesive film for a metal terminal, and a method for manufacturing the electric storage device will be described in detail below.

[0017] In this specification, the numerical range indicated by "to" means "greater than or equal to" or "less than or equal to." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0018] 1. Adhesive film for metal terminals The adhesive film for metal terminal of the present disclosure is interposed between a metal terminal electrically connected to an electrode of an electricity storage device element and an exterior material for an electricity storage device that seals the electricity storage device element. Specifically, as shown in, for example, FIG. 1 to FIG. 3, the adhesive film for metal terminal 1 of the present disclosure is interposed between a metal terminal 2 electrically connected to an electrode of an electricity storage device element 4 and an exterior material for an electricity storage device 3 that seals the electricity storage device element 4. The metal terminal 2 protrudes outside the exterior material for an electricity storage device 3, and is sandwiched between the exterior material for an electricity storage device 3 via the adhesive film for metal terminal 1 at the peripheral portion 3a of the heat-sealed exterior material for an electricity storage device 3. In the present disclosure, the heating temperature when the exterior material for an electricity storage device is heat-sealed is usually in the range of about 160 to 190° C., and the pressure is usually in the range of about 1.0 to 2.0 MPa.

[0019] The adhesive film 1 for metal terminals of the present disclosure is provided to improve the adhesion between the metal terminal 2 and the exterior material 3 for an electricity storage device. By improving the adhesion between the metal terminal 2 and the exterior material 3 for an electricity storage device, the sealing property of the electricity storage device element 4 is improved. As described above, when the electricity storage device element 4 is heat-sealed, the electricity storage device element is sealed such that the metal terminal 2 electrically connected to the electrode of the electricity storage device element 4 protrudes to the outside of the exterior material 3 for an electricity storage device. At this time, the metal terminal 2 formed of metal and the heat-sealable resin layer 35 (a layer formed of a heat-sealable resin such as polyolefin) located in the innermost layer of the exterior material 3 for an electricity storage device are formed of different materials, so that if such an adhesive film is not used, the sealing property of the electricity storage device element is likely to be reduced at the interface between the metal terminal 2 and the heat-sealable resin layer 35.

[0020] The adhesive film 1 for metal terminal of the present disclosure may be a single layer as shown in FIG. 4, or may be a multilayer as shown in FIG. 5 to FIG. 8, as long as the value of the tensile modulus A after heating is smaller than the value of the tensile modulus B before heating, as described below. The adhesive film 1 for metal terminal of the present disclosure is preferably a multilayer. When the adhesive film 1 for metal terminal of the present disclosure is a multilayer, it is preferable that it includes at least a structure in which the substrate 11 and the first polyolefin layer 12a are laminated, as shown in FIG. 5 to FIG. 8, and it is more preferable that it includes at least a structure in which the first polyolefin layer 12a, the substrate 11, and the second polyolefin layer 12b are laminated in this order, as shown in FIG. 6 and FIG. 7. In addition, in the adhesive film 1 for metal terminal of the present disclosure, it is preferable that the first polyolefin layer 12a and the second polyolefin layer 12b are located on the surfaces of both sides, respectively.

[0021] In the adhesive film 1 for metal terminals of the present disclosure, at least one of the first polyolefin layer 12a and the second polyolefin layer 12b preferably contains an acid-modified polyolefin, and it is more preferable that the first polyolefin layer 12a and the second polyolefin layer 12b contain an acid-modified polyolefin. In addition, the base material 11 preferably contains a polyolefin. As described later, the first polyolefin layer 12a and the second polyolefin layer 12b are preferably acid-modified polypropylene layers formed from acid-modified polypropylene. In addition, the base material 11 is preferably a polypropylene layer formed from polypropylene.

[0022] Specific examples of preferred laminate structures for the adhesive film 1 for metal terminals of the present disclosure include a two-layer structure of acid-modified polypropylene layer / polypropylene layer; a three-layer structure in which an acid-modified polypropylene layer / polypropylene layer / acid-modified polypropylene layer are laminated in this order; and a five-layer structure in which an acid-modified polypropylene layer / polypropylene layer / acid-modified polypropylene layer / polypropylene layer / acid-modified polypropylene layer are laminated in this order. Of these, a two-layer structure of acid-modified polypropylene layer / polypropylene layer; and a three-layer structure in which an acid-modified polypropylene layer / polypropylene layer / acid-modified polypropylene layer are laminated in this order are more preferred, and a three-layer structure in which an acid-modified polypropylene layer / polypropylene layer / acid-modified polypropylene layer are laminated in this order are particularly preferred.

[0023] When the adhesive film 1 for metal terminals of the present disclosure is placed between the metal terminal 2 of the electricity storage device 10 and the exterior material 3 for the electricity storage device, the surface of the metal terminal 2 made of metal and the heat-sealable resin layer 35 (a layer formed of a heat-sealable resin such as polyolefin) of the exterior material 3 for the electricity storage device are adhered via the adhesive film 1 for metal terminals.

[0024] In the adhesive film 1 for metal terminal of the present disclosure, the value of tensile modulus A after heating described below is smaller than the value of tensile modulus B before heating described below. Tensile modulus A after heating: The tensile modulus measured in an environment at a temperature of 25°C after leaving the sample to stand for 12 seconds in a heated environment at a temperature of 140°C and then leaving the sample to stand for one hour in an environment at a temperature of 25°C. Tensile modulus B before heating: Tensile modulus measured in an environment at a temperature of 25°C.

[0025] From the viewpoint of exhibiting higher adhesive strength to a metal terminal even when the heating temperature when adhering to the metal terminal is low, for example, from 140° C. to 180° C., the tensile modulus A is preferably about 580 MPa or more, more preferably about 600 MPa or more, further preferably about 650 MPa or more, and is preferably about 700 MPa or less, and preferred ranges include about 580 to 700 MPa, about 600 to 700 MPa, and about 650 to 700 MPa. The method for measuring the tensile modulus A is as follows.

[0026] <Tensile modulus A after heating> The tensile modulus after heating for 12 seconds at a temperature of 140°C is measured by the following procedure. First, the adhesive film for metal terminals is cut into strips with a width (TD) of 15 mm and a length (MD) of 50 mm. Next, it is placed on a hot plate heated to 140°C, left to stand for 12 seconds, and then immediately left to stand for 1 hour under atmospheric pressure and in a 25°C environment to obtain a test piece. Next, a stress-strain curve of the test piece is obtained using a Tensilon universal material testing machine (e.g., RTG-1210 manufactured by A&D Co., Ltd.) under atmospheric pressure and in a 25°C environment under conditions of a tensile speed of 300 mm / min and a chuck distance of 30 mm, and the tensile modulus A of the adhesive film for metal terminals after heating is obtained from the slope of the straight line connecting the two points of 0.05% and 0.25% strain.

[0027] From the viewpoint of exhibiting higher adhesive strength to the metal terminal even if the heating temperature when adhering to the metal terminal is low, for example, from 140°C to 180°C, the tensile modulus after heating for 12 seconds at a temperature of 160°C is preferably about 600 MPa or more, more preferably about 650 MPa or more, even more preferably about 680 MPa or more, and also preferably about 780 MPa or less, with preferred ranges being about 600 to 780 MPa, about 650 to 780 MPa, and about 680 to 700 MPa. The method for measuring the tensile modulus after heating for 12 seconds at a temperature of 160°C is similar to that of the above <Tensile modulus after heating A>, except that the adhesive film for metal terminal is placed on a hot plate heated to 160°C.

[0028] From the viewpoint of exhibiting higher adhesive strength to the metal terminal even if the heating temperature when adhering to the metal terminal is low, for example, from 140°C to 180°C, the tensile modulus after heating for 12 seconds at a temperature of 180°C is preferably about 500 MPa or more, more preferably about 520 MPa or more, even more preferably about 550 MPa or more, and also preferably about 750 MPa or less, with preferred ranges being about 500 to 750 MPa, about 520 to 750 MPa, and about 550 to 750 MPa. The method for measuring the tensile modulus after heating for 12 seconds at a temperature of 180°C is similar to that of the above <Tensile modulus after heating A>, except that the adhesive film for metal terminal is placed on a hot plate heated to 180°C.

[0029] The adhesive film 1 for metal terminal of the present disclosure has a tensile modulus B measured in an environment at a temperature of 25°C before being exposed to a heating environment of preferably about 580 MPa or more, more preferably about 650 MPa or more, even more preferably about 700 MPa or more, and even more preferably about 750 MPa or more, and is preferably about 900 MPa or less, more preferably about 800 MPa or less, and preferred ranges include about 580 to 900 MPa, about 650 to 900 MPa, about 700 to 900 MPa, about 750 to 900 MPa, about 580 to 800 MPa, about 650 to 800 MPa, about 700 to 800 MPa, and about 750 to 800 MPa. The method for measuring the tensile modulus B is as follows.

[0030] <Tensile modulus B before heating> In accordance with the provisions of JIS K7161-1 (ISO527-1), the tensile modulus B of the adhesive film for metal terminals (the adhesive film for metal terminals before heating in the above-mentioned <tensile modulus A after heating>) in a 25°C environment is measured. Specifically, the adhesive film for metal terminals is cut into strips with a width (TD) of 15 mm and a length (MD) of 50 mm. Next, for the adhesive film for metal terminals, a stress-strain curve of the test piece is obtained in a 25°C environment using a Tensilon universal material testing machine (e.g., RTG-1210 manufactured by A&D Co., Ltd.) under conditions of a tensile speed of 300 mm / min and a chuck distance of 30 mm, and the tensile modulus B of the adhesive film for metal terminals before heating is obtained from the slope of the straight line connecting the two points of 0.05% and 0.25% strain.

[0031] The tensile modulus of the adhesive film for metal terminals 1 of the present disclosure can be adjusted by the laminate configuration, the melting point, MFR, thickness, thickness ratio of each layer, and further by the conditions of the T-die, inflation, etc. in the production of the adhesive film for metal terminals 1 (e.g., the extrusion width from the T-die, the stretching ratio, the stretching speed, the heat treatment temperature, etc.).

[0032] From the viewpoint of exerting a higher adhesive strength to a metal terminal even when the heating temperature when adhering to the metal terminal is low, for example, from 140°C to 180°C, the adhesive film 1 for metal terminal of the present disclosure has a tensile modulus difference calculated by subtracting the value of the tensile modulus B from the value of the tensile modulus A ((difference in tensile modulus) = "value of tensile modulus A after heating" - "value of tensile modulus B before heating") of preferably about -20 MPa or less (i.e., (difference in tensile modulus) ≦ -20 MPa), more preferably about -50 MPa or less, and even more preferably about -70 MPa or less. The difference in tensile modulus is preferably about -150 MPa or more. Preferred ranges of the difference in tensile modulus include about -20 to -150 MPa, about -50 to -150 MPa, and about -70 to -150 MPa.

[0033] The total thickness of the adhesive film 1 for metal terminal of the present disclosure is, for example, about 120 μm or more, preferably about 140 μm or more, and more preferably about 150 μm or more, from the viewpoint of exhibiting higher adhesive strength to the metal terminal even at a low heating temperature of, for example, 140° C. to 180° C. when adhering to the metal terminal while satisfying the above-mentioned tensile elastic modulus. The upper limit of the total thickness of the adhesive film 1 for metal terminal of the present disclosure is, for example, about 200 μm. The preferred range of the total thickness of the adhesive film 1 for metal terminal of the present disclosure is about 120 to 200 μm, about 140 to 200 μm, or about 150 to 200 μm.

[0034] <When the adhesive film for metal terminal according to the present disclosure is a single layer> When the adhesive film for metal terminal of the present disclosure is a single layer, the adhesive film for metal terminal 1 of the present disclosure is preferably composed of a first polyolefin layer 12a having the physical properties described above.

[0035] <When the adhesive film for metal terminal of the present disclosure is multilayered> When the adhesive film for metal terminal of the present disclosure is a multilayer film, the adhesive film for metal terminal 1 of the present disclosure preferably includes at least a structure in which a substrate 11 and a first polyolefin layer 12a are laminated together, and is a laminate having the characteristics described above, and preferably includes at least a structure in which a first polyolefin layer 12a, a substrate 11, and a second polyolefin layer 12b are laminated together in this order, and is a laminate having the characteristics described above.

[0036] The substrate 11, the first polyolefin layer 12a, and the second polyolefin layer 12b will be described in detail below.

[0037] [Base material 11] In the adhesive film for metal terminal 1, the substrate 11 is a layer that functions as a support for the adhesive film for metal terminal 1, and is provided as necessary.

[0038] The material forming the substrate 11 is not particularly limited. Examples of the material forming the substrate 11 include polyolefin, polyamide, polyester, epoxy resin, acrylic resin, fluororesin, silicone resin, phenol resin, polyetherimide, polyimide, polycarbonate, and mixtures and copolymers thereof, among which polyolefin is particularly preferred. That is, the material forming the substrate 11 is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. The inclusion of a polyolefin skeleton in the resin constituting the substrate 11 can be analyzed by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like.

[0039] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; crystalline or amorphous polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and ethylene-butene-propylene terpolymers. Among these polyolefins, polyethylene and polypropylene are preferred, and polypropylene is more preferred.

[0040] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid, and aromatic polyamides such as polymetaxylylene adipamide (MXD6); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); polyamides copolymerized with lactam components and isocyanate components such as 4,4'-diphenylmethane-diisocyanate, polyesteramide copolymers and polyetheresteramide copolymers which are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and copolymers thereof. These polyamides may be used alone or in combination of two or more.

[0041] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolymerized polyesters mainly composed of ethylene terephthalate as repeating units, copolymerized polyesters mainly composed of butylene terephthalate as repeating units, etc. Specific examples of copolymerized polyesters mainly composed of ethylene terephthalate as repeating units include copolymer polyesters in which ethylene terephthalate as a main repeating unit is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decane dicarboxylate), etc. Specific examples of copolymer polyesters containing butylene terephthalate as the main repeating unit include copolymer polyesters in which butylene terephthalate is the main repeating unit and is polymerized with butylene isophthalate (hereinafter abbreviated as polybutylene (terephthalate / isophthalate)), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters may be used alone or in combination of two or more.

[0042] The substrate 11 may be made of a nonwoven fabric made of the above-mentioned resin. When the substrate 11 is a nonwoven fabric, the substrate 11 is preferably made of the above-mentioned polyolefin, polyamide, or the like.

[0043] As described above, the substrate 11 can be made into a layer containing a colorant by blending a colorant in the substrate 11. Also, the light transmittance can be adjusted by selecting a resin with low transparency. When the substrate 11 is a film, a colored film or a film with low transparency can be used. When the substrate 11 is a nonwoven fabric, a nonwoven fabric using a fiber or binder containing a colorant or a nonwoven fabric with low transparency can be used.

[0044] The melt mass flow rate (MFR) of the substrate 11 at 230 ° C. is preferably 8 g / 10 min or less, more preferably 4 g / 10 min or less, from the viewpoint of exhibiting higher adhesive strength to the metal terminal even at a low heating temperature of, for example, 140 ° C. to 180 ° C. when adhering to the metal terminal while satisfying the tensile modulus described above, and is preferably 1 g / 10 min or more, more preferably 2 g / 10 min or more, from the viewpoint of obtaining an adhesive film 1 for a metal terminal having excellent flexibility (good evaluation in a bending test described later). Preferred ranges include about 1 to 8 g / 10 min, about 1 to 4 g / 10 min, about 2 to 8 g / 10 min, and about 2 to 4 g / 10 min. The melt mass flow rate (MFR) of the substrate 11 is a value (g / 10 min) at 230 ° C. measured in accordance with the provisions of JIS K7210-1:2014 (ISO 1133-1:2011).

[0045] The melting point of the substrate 11 is preferably 130° C. or higher, more preferably 150° C. or higher, from the viewpoint of exhibiting higher adhesive strength to the metal terminal even when the heating temperature during bonding to the metal terminal is low, for example, from 140° C. to 180° C., while still satisfying the above-mentioned tensile elastic modulus, and is preferably 190° C. or lower, more preferably 170° C. or lower, with preferred ranges being about 130 to 190° C., or about 150 to 170° C., from the viewpoint of providing an adhesive film 1 for metal terminals with excellent flexibility. The melting point of the substrate 11 is measured by the method described in the Examples.

[0046] When the substrate 11 is made of a resin film, the surface of the substrate 11 may be subjected to a known adhesion enhancing treatment such as corona discharge treatment, ozone treatment, or plasma treatment, if necessary.

[0047] The thickness of the substrate 11 is preferably about 40 μm or more, more preferably about 50 μm or more, even more preferably about 55 μm or more, and even more preferably about 60 μm or more, and is preferably about 120 μm or less, more preferably about 100 μm or less, and even more preferably about 85 μm or less, and examples of the thickness include about 40 to 120 μm, about 40 to 100 μm, about 40 to 85 μm, about 50 to 120 μm, about 50 to 100 μm, about 50 to 85 μm, about 55 to 120 μm, about 55 to 100 μm, about 55 to 85 μm, about 60 to 120 μm, about 60 to 100 μm, and about 60 to 85 μm. Among these, about 60 to 100 μm is particularly preferable.

[0048] [First and second polyolefin layers 12a, 12b] The adhesive film 1 for metal terminal of the present disclosure preferably includes a first polyolefin layer 12a. When the adhesive film 1 for metal terminal of the present disclosure is composed of a single layer, the adhesive film 1 for metal terminal is preferably composed of a first polyolefin layer 12a as shown in FIG. 4. When the adhesive film 1 for metal terminal of the present disclosure is composed of multiple layers, it is preferable that the adhesive film 1 for metal terminal includes at least a structure in which the substrate 11 and the first polyolefin layer 12a are laminated, and more preferably includes a structure in which at least the first polyolefin layer 12a, the substrate 11, and the second polyolefin layer 12b are laminated in this order as shown in FIGS. 6 and 7. In the adhesive film 1 for metal terminal of the present disclosure, the first polyolefin layer 12a and the second polyolefin layer 12b are preferably located on the surfaces of both sides, respectively.

[0049] In addition, at least one of the first polyolefin layer 12a and the second polyolefin layer 12b preferably contains an acid-modified polyolefin, and it is more preferable that the first polyolefin layer 12a and the second polyolefin layer 12b contain an acid-modified polyolefin. In some cases, at least one of the first and second polyolefin layers 12a and 12b is formed of an acid-modified polyolefin, one of the first and second polyolefin layers 12a and 12b is formed of an acid-modified polyolefin and the other is formed of a polyolefin, or both the first and second polyolefin layers 12a and 12b are formed of an acid-modified polyolefin. Acid-modified polyolefins have a high affinity with metals and heat-sealing resins such as polyolefins. In addition, polyolefins have a high affinity with heat-sealing resins such as polyolefins. Therefore, in the adhesive film 1 for metal terminals of the present disclosure, by disposing a layer formed of an acid-modified polyolefin on the metal terminal 2 side, excellent adhesion can be exhibited at the interface between the adhesive film 1 for metal terminals and the metal terminal 2 and the heat-sealing resin layer 35.

[0050] The adhesive film 1 for metal terminals is preferably a laminate having a first polyolefin layer 12a, a substrate 11, and a second polyolefin layer 12b in this order. The adhesive film 1 for metal terminals has a laminate structure in which the first polyolefin layer 12a / substrate 11 / second polyolefin layer 12b are laminated in this order, for example, as shown in Figures 6 and 7. As described above, the adhesive film 1 for metal terminals is particularly preferably a three-layer structure in which an acid-modified polypropylene layer / polypropylene layer / acid-modified polypropylene layer are laminated in this order.

[0051] In the first and second polyolefin layers 12a and 12b, the acid-modified polyolefin is not particularly limited as long as it is an acid-modified polyolefin, but preferred examples include polyolefins graft-modified with an unsaturated carboxylic acid or anhydride thereof.

[0052] Specific examples of polyolefins to be modified with an acid include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; crystalline or amorphous polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and ethylene-butene-propylene terpolymers. Among these polyolefins, polyethylene and polypropylene are preferable.

[0053] The polyolefin to be acid-modified may be a cyclic polyolefin. For example, a carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or an anhydride thereof, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or an anhydride thereof to the cyclic polyolefin.

[0054] The acid-modified cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins that are the constituent monomers of the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Examples of the cyclic monomers that are the constituent monomers of the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these polyolefins, preferred are cyclic alkenes, and more preferred are norbornene. Another example of the constituent monomer is styrene.

[0055] Examples of the carboxylic acid or anhydride thereof used for the acid modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0056] When either the first or second polyolefin layer 12a, 12b is formed from a polyolefin, examples of the polyolefin include the same as those exemplified above as the acid-modified polyolefin or the acid-modified cyclic polyolefin.

[0057] Each of the first and second polyolefin layers 12a and 12b may be formed of one type of resin component alone or a blend polymer of two or more types of resin components. Furthermore, each of the first and second polyolefin layers 12a and 12b may be formed of only one layer or two or more layers of the same or different resin components.

[0058] Furthermore, the first and second polyolefin layers 12a and 12b may each contain a filler as necessary. When the first and second polyolefin layers 12a and 12b contain a filler, the filler functions as a spacer, making it possible to effectively suppress a short circuit between the metal terminal 2 and the barrier layer 33 of the exterior material 3 for a power storage device. The particle size of the filler may be in the range of about 0.1 to 35 μm, preferably about 5.0 to 30 μm, and more preferably about 10 to 25 μm. The content of the filler may be about 5 to 30 parts by mass, and more preferably about 10 to 20 parts by mass, relative to 100 parts by mass of the resin component forming the first and second polyolefin layers 12a and 12b.

[0059] As the filler, either inorganic or organic can be used. Examples of inorganic fillers include carbon (carbon, graphite), silica, aluminum oxide, barium titanate, iron oxide, silicon carbide, zirconium oxide, zirconium silicate, magnesium oxide, titanium oxide, calcium aluminate, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, etc. Examples of organic fillers include fluororesin, phenolic resin, urea resin, epoxy resin, acrylic resin, benzoguanamine-formaldehyde condensate, melamine-formaldehyde condensate, polymethyl methacrylate crosslinked product, polyethylene crosslinked product, etc. From the viewpoints of shape stability, rigidity, and content resistance, aluminum oxide, silica, fluororesin, acrylic resin, and benzoguanamine-formaldehyde condensate are preferred, and among these, spherical aluminum oxide and silica are more preferred. As a method for mixing the filler into the resin component forming the polyolefin layer 12, a method in which the two are melt-blended in advance using a Banbury mixer or the like to prepare a master batch and then adjusted to a predetermined mixing ratio, or a method in which the filler is directly mixed with the resin component can be used.

[0060] In addition, the first and second polyolefin layers 12a and 12b may each contain a pigment as necessary. As the pigment, various inorganic pigments can be used. As a specific example of the pigment, carbon (carbon, graphite) exemplified as the above filler can be preferably exemplified. Carbon (carbon, graphite) is a material generally used inside an electricity storage device, and there is no risk of it dissolving in the electrolyte. In addition, it has a large coloring effect, and a sufficient coloring effect can be obtained with an added amount that does not inhibit adhesion, and it does not melt by heat, and the apparent melt viscosity of the added resin can be increased. Furthermore, it is possible to prevent the pressurized part from becoming thin during heat adhesion (heat sealing), and to impart excellent sealing properties between the exterior material for electricity storage devices and the metal terminal.

[0061] When a pigment is added to the first and second polyolefin layers 12a and 12b, the amount of the pigment added is, for example, about 0.05 to 0.3 parts by mass, preferably about 0.1 to 0.2 parts by mass, per 100 parts by mass of the resin components forming the first and second polyolefin layers 12a and 12b, when carbon black with a particle size of about 0.03 μm is used. By adding a pigment to the first and second polyolefin layers 12a and 12b, the presence or absence of the adhesive film for metal terminal 1 can be detected by a sensor or visually inspected. When a filler and a pigment are added to the first and second polyolefin layers 12a and 12b, the filler and the pigment may be added to the same first and second polyolefin layers 12a and 12b, but from the viewpoint of not impairing the thermal fusion property of the adhesive film for metal terminal 1, it is preferable to add the filler and the pigment separately to the first and second polyolefin layers 12a and 12b.

[0062] The first and second polyolefin layers 12a, 12b can be made of a polyolefin film or an acid-modified polyolefin film, respectively. When the first and second polyolefin layers 12a, 12b are made of a polyolefin film or an acid-modified polyolefin film, the adhesive film for metal terminals can be suitably manufactured by laminating a resin film formed of the above polyolefin or acid-modified polyolefin on the substrate 11 using, for example, a dry lamination method. Also, the adhesive film for metal terminals can be suitably manufactured by extruding the resin constituting the first and second polyolefin layers 12a, 12b onto the substrate 11.

[0063] The melt mass flow rate (MFR) of the first and second polyolefin layers 12a, 12b at 230°C is preferably about 6.5 g / 10 min or more, more preferably about 7 g / 10 min or more, and even more preferably about 8 g / 10 min or more, from the viewpoint of exhibiting higher adhesive strength to a metal terminal even at a low heating temperature of, for example, 140°C to 180°C when being bonded to a metal terminal while satisfying the above-mentioned tensile elastic modulus. The melt mass flow rate (MFR) of the first and second polyolefin layers 12a and 12b is preferably about 11 g / 10 min or less, more preferably about 10 g / 10 min or less, and even more preferably about 8.5 g / 10 min or less, and examples of the melt mass flow rate (MFR) of the first and second polyolefin layers 12a and 12b are values ​​(g / 10 min) at 230° C. measured in accordance with the provisions of JIS K7210-1:2014 (ISO 1133-1:2011).

[0064] The melting points of the first and second polyolefin layers 12a, 12b are preferably about 120° C. or higher, more preferably about 130° C. or higher, and preferably about 160° C. or lower, more preferably about 150° C. or lower, with preferred ranges being about 120 to 160° C., about 120 to 150° C., about 130 to 160° C., or about 130 to 150° C., from the viewpoint of exhibiting higher adhesive strength to the metal terminal even when the heating temperature during bonding to the metal terminal is low, for example, from 140° C. to 180° C. while satisfying the above-mentioned tensile elastic modulus. The melting points of the first and second polyolefin layers 12a, 12b are measured by the method described in the Examples.

[0065] When the first and second polyolefin layers 12a, 12b made of resin films are laminated on the surface of the substrate 11, the surfaces of the first and second polyolefin layers 12a, 12b facing the substrate 11 may be subjected to a known adhesion enhancing means such as corona discharge treatment, ozone treatment, plasma treatment, etc. In particular, by subjecting the surfaces to corona discharge treatment, the adhesion between the substrate 11 and the first polyolefin layer 12a and the second polyolefin layer 12b is improved, and excellent sealing properties can be imparted between the exterior material for an electricity storage device and the metal terminal.

[0066] The thickness of the first and second polyolefin layers 12a, 12b is preferably about 20 μm or more, more preferably about 30 μm or more, and even more preferably about 35 μm or more, and is preferably about 60 μm or less, and more preferably about 50 μm or less, from the viewpoint of exhibiting higher adhesive strength to a metal terminal even when the heating temperature when bonding to the metal terminal is low, for example, from 140° C. to 180° C. Preferable ranges of the thickness of the first and second polyolefin layers 12a, 12b include about 20 to 60 μm, about 20 to 50 μm, about 30 to 60 μm, about 30 to 50 μm, about 35 to 60 μm, and about 35 to 50 μm, respectively.

[0067] The ratio of the thickness of the substrate 11 to the total thickness of the first and second polyolefin layers 12a, 12b is preferably 0.5 or more, more preferably 0.7 or more, and even more preferably 0.8 or more, from the viewpoint of exhibiting higher adhesive strength to the metal terminal even when the heating temperature when bonding to the metal terminal is a low temperature of, for example, 140°C to 180°C, while satisfying the above-mentioned tensile elastic modulus, and is preferably 1.5 or less, more preferably 1.2 or less, and preferred ranges include about 0.5 to 1.5, about 0.5 to 1.2, about 0.7 to 1.5, about 0.7 to 1.2, about 0.8 to 1.5, and about 0.8 to 1.2.

[0068] [Adhesion promoter layer 13] The adhesion promoter layer 13 is a layer that is provided as necessary for the purpose of firmly adhering the substrate 11 to the first and second polyolefin layers 12a, 12b (see FIG. 7). The adhesion promoter layer 13 may be provided on only one side between the substrate 11 and the first and second polyolefin layers 12a, 12b, or on both sides.

[0069] The adhesion promoter layer 13 can be formed using known adhesion promoters such as isocyanate-based, polyethyleneimine-based, polyester-based, polyurethane-based, polybutadiene-based, etc. From the viewpoint of further improving the electrolyte resistance, it is preferable to form the adhesion promoter using an isocyanate-based adhesion promoter. As the isocyanate-based adhesion promoter, one made of an isocyanate component selected from triisocyanate monomer and polymeric MDI has excellent laminate strength and shows little decrease in laminate strength after immersion in electrolyte. It is particularly preferable to form the adhesive using an adhesion promoter made of triphenylmethane-4,4',4"-triisocyanate, which is a triisocyanate monomer, or polymethylene polyphenyl polyisocyanate, which is a polymeric MDI (NCO content of approximately 30%, viscosity of 200 to 700 mPa s). It is also preferable to form the adhesive using a two-component curing adhesion promoter that uses tris(p-isocyanatephenyl)thiophosphate, which is a triisocyanate monomer, or a polyethyleneimine-based agent as the main agent and polycarbodiimide as the crosslinking agent.

[0070] The adhesion promoter layer 13 can be formed by coating and drying using a known coating method such as bar coating, roll coating, gravure coating, etc. The coating amount of the adhesion promoter is 20 to 100 mg / m in the case of an adhesion promoter made of triisocyanate. 2 Approximately, preferably 40 to 60 mg / m 2 In the case of adhesion promoters made of polymeric MDI, the concentration is 40 to 150 mg / m 2 Approximately, preferably 60 to 100 mg / m 2In the case of a two-component curing adhesion promoter that uses polyethyleneimine as the base agent and polycarbodiimide as the crosslinking agent, the adhesive strength is about 5 to 50 mg / m 2 Approximately, preferably 10 to 30 mg / m 2 Triisocyanate monomer is a monomer with three isocyanate groups in one molecule, and polymeric MDI is a mixture of MDI and MDI oligomers formed by polymerization of MDI, and is represented by the following formula:

[0071] [ka]

[0072] The adhesive film 1 for metal terminals of the present disclosure can be produced, for example, by laminating the first and second polyolefin layers 12a, 12b, respectively, on both surfaces of the substrate 11. The substrate 11 and the first and second polyolefin layers 12a, 12b can be laminated by a known method such as extrusion lamination or thermal lamination. In addition, when the substrate 11 and the first and second polyolefin layers 12a, 12 are laminated via the adhesion promoter layer 13, for example, the adhesion promoter constituting the adhesion promoter layer 13 is applied and dried on the substrate 11 by the above-mentioned method, and the first and second polyolefin layers 12a, 12b are laminated on the adhesion promoter layer 13, respectively.

[0073] The method for interposing the adhesive film 1 for a metal terminal between the metal terminal 2 and the exterior material 3 for an electricity storage device is not particularly limited, and for example, as shown in Figures 1 to 3, the adhesive film 1 for a metal terminal may be wrapped around the metal terminal 2 in a portion where the metal terminal 2 is sandwiched by the exterior material 3 for an electricity storage device. Furthermore, although not shown, in a portion where the metal terminal 2 is sandwiched by the exterior material 3 for an electricity storage device, the adhesive film 1 for a metal terminal may be disposed on both sides of the metal terminal 2 so as to cross the two metal terminals 2.

[0074] [Metal terminal 2] The adhesive film 1 for metal terminals of the present disclosure is used by being interposed between a metal terminal 2 and an exterior material 3 for an electricity storage device. The metal terminal 2 is a conductive member electrically connected to an electrode (positive electrode or negative electrode) of an electricity storage device element 4, and is made of a metal material. The metal material constituting the metal terminal 2 is not particularly limited, and examples thereof include aluminum, nickel, copper, and the like. For example, the metal terminal 2 connected to the positive electrode of a lithium ion electricity storage device is usually made of aluminum, etc. Furthermore, the metal terminal connected to the negative electrode of a lithium ion electricity storage device is usually made of copper, nickel, etc.

[0075] From the viewpoint of enhancing electrolyte resistance, it is preferable that the surface of the metal terminal 2 is subjected to a chemical conversion treatment. For example, when the metal terminal 2 is made of aluminum, specific examples of the chemical conversion treatment include known methods for forming a corrosion-resistant film such as a phosphate, a chromate, a fluoride, or a triazine thiol compound. Among the methods for forming a corrosion-resistant film, a phosphate chromate treatment using a material composed of three components: a phenolic resin, a chromium (III) fluoride compound, and phosphoric acid is preferable.

[0076] The size of the metal terminal 2 may be appropriately set depending on the size of the electricity storage device to be used. The thickness of the metal terminal 2 is preferably about 50 to 1000 μm, more preferably about 70 to 800 μm. The length of the metal terminal 2 is preferably about 1 to 200 mm, more preferably about 3 to 150 mm. The width of the metal terminal 2 is preferably about 1 to 200 mm, more preferably about 3 to 150 mm.

[0077] [Exterior materials for energy storage devices 3] The exterior material 3 for an electricity storage device may have a laminated structure including at least a base material layer 31, a barrier layer 33, and a heat-sealable resin layer 35 in this order. FIG. 8 shows an example of a cross-sectional structure of the exterior material 3 for an electricity storage device, in which the base material layer 31, an adhesive layer 32 provided as needed, a barrier layer 33, an adhesive layer 34 provided as needed, and a heat-sealable resin layer 35 are laminated in this order. In the exterior material 3 for an electricity storage device, the base material layer 31 is the outer layer, and the heat-sealable resin layer 35 is the innermost layer. When assembling the electricity storage device, the heat-sealable resin layers 35 located on the periphery of the electricity storage device element 4 are brought into contact with each other and heat-sealed to seal the electricity storage device element 4, thereby sealing the electricity storage device element 4. Note that FIGS. 1 to 3 show an electricity storage device 10 using an embossed type exterior material 3 for an electricity storage device formed by embossing or the like, but the exterior material 3 for an electricity storage device may be an unformed pouch type. The pouch type includes three-sided seal, four-sided seal, pillow type, etc., and any type may be used.

[0078] The thickness of the laminate constituting the electricity storage device exterior material 3 is not particularly limited, but the upper limit, from the viewpoints of cost reduction, energy density improvement, and the like, is preferably about 180 μm or less, about 160 μm or less, about 155 μm or less, about 140 μm or less, about 130 μm or less, and about 120 μm or less. The lower limit, from the viewpoint of maintaining the function of the electricity storage device exterior material 3 to protect the electricity storage device element 4, is preferably about 35 μm or more, about 45 μm or more, about 60 μm or more, and about 80 μm or more. Preferred ranges include, for example, about 35 to 180 μm, 35 to 1 Examples of the thickness include about 60 μm, about 35 to 155 μm, about 35 to 140 μm, about 35 to 130 μm, about 35 to 120 μm, about 45 to 180 μm, about 45 to 160 μm, about 45 to 155 μm, about 45 to 140 μm, about 45 to 130 μm, about 45 to 120 μm, about 60 to 180 μm, about 60 to 160 μm, about 60 to 155 μm, about 60 to 140 μm, about 60 to 130 μm, about 60 to 120 μm, about 80 to 180 μm, about 80 to 160 μm, about 80 to 155 μm, about 80 to 140 μm, about 80 to 130 μm, and about 80 to 120 μm.

[0079] (Base material layer 31) In the packaging material 3 for an electricity storage device, the base material layer 31 is a layer that functions as the base material of the packaging material for an electricity storage device, and is a layer that forms the outermost layer side.

[0080] The material for forming the base layer 31 is not particularly limited, as long as it has insulating properties. Examples of materials for forming the base layer 31 include polyester, polyamide, epoxy, acrylic, fluororesin, polyurethane, silicone resin, phenol, polyetherimide, polyimide, and mixtures and copolymers thereof. Polyesters such as polyethylene terephthalate and polybutylene terephthalate have the advantage of being excellent in electrolyte resistance and being unlikely to cause whitening due to adhesion of electrolyte, and are preferably used as materials for forming the base layer 31. In addition, polyamide films have excellent stretchability and can prevent whitening due to resin cracking of the base layer 31 during molding, and are preferably used as materials for forming the base layer 31.

[0081] The base layer 31 may be formed of a uniaxially or biaxially stretched resin film, or may be formed of an unstretched resin film. Among them, a uniaxially or biaxially stretched resin film, especially a biaxially stretched resin film, is preferably used as the base layer 31 because its heat resistance is improved by oriented crystallization.

[0082] Among these, the resin film forming the base layer 31 is preferably nylon or polyester, and more preferably biaxially oriented nylon or biaxially oriented polyester.

[0083] The base layer 31 may be laminated with resin films of different materials in order to improve pinhole resistance and insulation when used as a package for a power storage device. Specific examples include a multi-layer structure in which a polyester film and a nylon film are laminated, and a multi-layer structure in which a biaxially oriented polyester and a biaxially oriented nylon are laminated. When the base layer 31 has a multi-layer structure, each resin film may be bonded via an adhesive, or may be directly laminated without an adhesive. When bonding without an adhesive, examples of the method include a method of bonding in a hot melt state, such as a co-extrusion method, a sand lamination method, and a thermal lamination method.

[0084] The base layer 31 may be made to have low friction in order to improve formability. When making the base layer 31 low-friction, the coefficient of friction of the surface is not particularly limited, but may be, for example, 1.0 or less. To make the base layer 31 low-friction, for example, matte treatment, formation of a thin film layer of a slip agent, a combination of these, etc. may be used.

[0085] The thickness of the base layer 31 is, for example, about 10 to 50 μm, and preferably about 15 to 30 μm.

[0086] (Adhesive layer 32) In the exterior material 3 for an electricity storage device, the adhesive layer 32 is a layer that is disposed on the base material layer 31 as necessary in order to impart adhesion to the base material layer 31. That is, the adhesive layer 32 is provided between the base material layer 31 and the barrier layer 33.

[0087] The adhesive layer 32 is formed of an adhesive capable of bonding the base material layer 31 and the barrier layer 33. The adhesive used to form the adhesive layer 32 may be a two-component curing adhesive or a one-component curing adhesive. The adhesion mechanism of the adhesive used to form the adhesive layer 32 is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like.

[0088] The resin component of the adhesive that can be used to form the adhesive layer 32 is preferably a polyurethane-based two-component curing adhesive; or a blend resin of polyamide, polyester, or these with modified polyolefin, from the viewpoint of having excellent ductility, durability under high humidity conditions, yellowing prevention, and thermal degradation prevention during heat sealing, and of effectively suppressing a decrease in the laminate strength between the base layer 31 and the barrier layer 33 and preventing the occurrence of delamination.

[0089] The adhesive layer 32 may be multi-layered with different adhesive components. When the adhesive layer 32 is multi-layered with different adhesive components, it is preferable to select a resin having excellent adhesion to the base material layer 31 as the adhesive component arranged on the base material layer 31 side, and an adhesive component having excellent adhesion to the barrier layer 33 as the adhesive component arranged on the barrier layer 33 side, from the viewpoint of improving the laminate strength between the base material layer 31 and the barrier layer 33. When the adhesive layer 32 is multi-layered with different adhesive components, specifically, the adhesive component arranged on the barrier layer 33 side is preferably an acid-modified polyolefin, a metal-modified polyolefin, a mixed resin of polyester and acid-modified polyolefin, a resin containing a copolymerized polyester, or the like.

[0090] The thickness of the adhesive layer 32 is, for example, about 2 to 50 μm, and preferably about 3 to 25 μm.

[0091] (Barrier layer 33) In the exterior material for a power storage device, the barrier layer 33 is a layer that has a function of preventing water vapor, oxygen, light, and the like from penetrating into the interior of the power storage device in addition to improving the strength of the exterior material for a power storage device. The barrier layer 33 is preferably a metal layer, that is, a layer formed of a metal. Specific examples of the metal constituting the barrier layer 33 include aluminum, stainless steel, and titanium, and aluminum is preferred. The barrier layer 33 can be formed, for example, of a metal foil, a metal vapor deposition film, an inorganic oxide vapor deposition film, a carbon-containing inorganic oxide vapor deposition film, or a film provided with these vapor deposition films, and is preferably formed of a metal foil, and more preferably formed of an aluminum foil. From the viewpoint of preventing the occurrence of wrinkles or pinholes in the barrier layer 33 during the manufacture of the exterior material for an electricity storage device, it is more preferable that the barrier layer be formed from a soft aluminum foil such as annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O).

[0092] The thickness of the barrier layer 33 is preferably about 10 to 200 μm, and more preferably about 20 to 100 μm, from the viewpoint of making the exterior material for an electricity storage device thinner and less likely to cause pinholes when molded.

[0093] Moreover, it is preferable that at least one surface, and preferably both surfaces, of the barrier layer 33 are subjected to a chemical conversion treatment in order to stabilize adhesion, prevent dissolution or corrosion, etc. Here, the chemical conversion treatment refers to a treatment for forming a corrosion-resistant film on the surface of the barrier layer.

[0094] (adhesive layer 34) In the packaging material 3 for an electricity storage device, the adhesive layer 34 is a layer that is provided, if necessary, between the barrier layer 33 and the heat-sealable resin layer 35 in order to firmly bond the heat-sealable resin layer 35.

[0095] The adhesive layer 34 is formed of an adhesive capable of bonding the barrier layer 33 and the heat-fusible resin layer 35. The composition of the adhesive used to form the adhesive layer is not particularly limited, and examples thereof include a resin composition containing an acid-modified polyolefin. Examples of the acid-modified polyolefin include the same ones as those exemplified for the first and second polyolefin layers 12a and 12b.

[0096] The thickness of the adhesive layer 34 is, for example, about 1 to 40 μm, and preferably about 2 to 30 μm.

[0097] (Thermal adhesive resin layer 35) In the electricity storage device packaging material 3, the heat-sealable resin layer 35 corresponds to the innermost layer, and is a layer that seals the electricity storage device elements by being heat-sealed to each other when the electricity storage device is assembled.

[0098] The resin component used in the heat-fusible resin layer 35 is not particularly limited as long as it is heat-fusible, and examples thereof include polyolefin and cyclic polyolefin.

[0099] Specific examples of the polyolefin include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; crystalline or amorphous polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and ethylene-butene-propylene terpolymers. Among these polyolefins, polyethylene and polypropylene are preferable.

[0100] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these polyolefins, preferred are cyclic alkenes, and more preferred are norbornene. Another example of the constituting monomer is styrene.

[0101] Among these resin components, preferred are crystalline or amorphous polyolefins, cyclic polyolefins, and blend polymers thereof; more preferred are polyethylene, polypropylene, copolymers of ethylene and norbornene, and blend polymers of two or more of these.

[0102] The thermally adhesive resin layer 35 may be formed of one type of resin component alone, or may be formed of a blend polymer of two or more types of resin components. Furthermore, the thermally adhesive resin layer 35 may be formed of only one layer, or may be formed of two or more layers of the same or different resin components.

[0103] The thickness of the heat-fusible resin layer 35 is not particularly limited, but may be about 2 to 2000 μm, preferably about 5 to 1000 μm, and more preferably about 10 to 500 μm.

[0104] 2. Energy storage device 10 The electricity storage device 10 of the present disclosure comprises at least an electricity storage device element 4 having a positive electrode, a negative electrode, and an electrolyte, an exterior material for an electricity storage device 3 that seals the electricity storage device element 4, and a metal terminal 2 that is electrically connected to each of the positive electrode and the negative electrode and protrudes to the outside of the exterior material for an electricity storage device 3. The electricity storage device 10 of the present disclosure is characterized in that an adhesive film for a metal terminal 1 of the present disclosure is interposed between the metal terminal 2 and the exterior material for an electricity storage device 3. That is, the electricity storage device 10 of the present disclosure can be manufactured by a method including a step of interposing an adhesive film for a metal terminal 1 of the present disclosure between the metal terminal 2 and the exterior material for an electricity storage device 3.

[0105] Specifically, an electric storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered with an electric storage device exterior material 3 in a state in which metal terminals 2 connected to the positive and negative electrodes protrude outward, and an adhesive film 1 for metal terminals of the present disclosure is interposed between the metal terminals 2 and a heat-sealable resin layer 35, and the electric storage device element 4 is covered so that a flange portion (a region where the heat-sealable resin layers 35 contact each other, the peripheral portion 3a of the electric storage device exterior material) of the electric storage device exterior material is formed, and the heat-sealable resin layers 35 of the flange portion are heat-sealed to seal them, thereby providing an electric storage device 10 using the electric storage device exterior material 3. When the electric storage device element 4 is housed using the electric storage device exterior material 3, the heat-sealable resin layer 35 of the electric storage device exterior material 3 is used so as to be on the inside (the surface in contact with the electric storage device element 4).

[0106] The exterior material for an electric storage device of the present disclosure can be suitably used for an electric storage device such as a battery (including a condenser, a capacitor, etc.). The exterior material for an electric storage device of the present disclosure may be used for either a primary battery or a secondary battery, but is preferably a secondary battery. The type of secondary battery to which the exterior material for an electric storage device of the present disclosure is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, all-solid-state batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, examples of suitable applications of the exterior material for an electric storage device of the present disclosure include lithium ion batteries and lithium ion polymer batteries. EXAMPLES

[0107] The present disclosure will be described in detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the examples.

[0108] Examples 1-3 and Comparative Examples 1-10 <Production of adhesive film for metal terminals> A polypropylene film (hereinafter, sometimes referred to as "PP layer") having a melting point and MFR as shown in Table 1 and a thickness as shown in Table 2 was used as the substrate. Maleic acid-modified polypropylene (hereinafter, sometimes referred to as "PPa") having a melting point and melt mass flow rate (MFR) as shown in Table 1 was extruded on one side of the substrate with a T-die extruder to form a first polyolefin layer (PPa layer) having a thickness as shown in Table 2. Next, PPa was extruded on the other side of the substrate with a T-die extruder to form a second polyolefin layer (PPa layer) having a thickness as shown in Table 2, thereby obtaining an adhesive film for metal terminals in which a PPa layer / PP layer / PPa layer were laminated in this order.

[0109] The tensile modulus of the adhesive film for metal terminals shown in Table 2 was adjusted by adjusting the melting point, MFR, thickness, thickness ratio of the PPa layer and the PP layer, as well as the conditions of the T-die, inflation, etc. in the production of adhesive film for metal terminal 1 (for example, the extrusion width from the T-die, the stretching ratio, the stretching speed, the heat treatment temperature, etc.).

[0110] <Melt point measurement> The melting points of the PP layer and the PPa layer shown in Table 1 are values ​​measured by the following method. The melting peak temperature was measured twice using a differential scanning calorimeter (DSC, a differential scanning calorimeter Q200 manufactured by TA Instruments). Specifically, the PP layer or the PPa layer was held at -20°C for 10 minutes by differential scanning calorimetry (DSC) according to the procedure of JIS K7121:2012 (Method of measuring transition temperature of plastics (JIS K7121:1987 Supplement 1)), and the first melting peak temperature P (°C) was measured by heating from -20°C to 250°C at a heating rate of 10°C / min, and then held at 250°C for 10 minutes. Next, the temperature was lowered from 250°C to -20°C at a heating rate of 10°C / min, and held for 10 minutes. Furthermore, the temperature was raised from -20°C to 250°C at a heating rate of 10°C / min to measure the second melting peak temperature Q (°C). The flow rate of the nitrogen gas was 50 ml / min. Using the above procedure, the melting peak temperature P (°C) measured the first time and the melting peak temperature Q (°C) measured the second time were obtained, and the one with the maximum peak was taken as the melting point.

[0111] <Melt Mass Flow Rate (MFR)> The melt mass flow rates (MFR) of the PP layer and the PPa layer shown in Table 1 are values ​​(g / 10 min) at 230°C measured in accordance with the provisions of JIS K7210-1:2014 (ISO 1133-1:2011).

[0112] [Table 1]

[0113] <Tensile modulus B before heating> In accordance with the provisions of JIS K7161-1 (ISO527-1), the tensile modulus B of the adhesive film for metal terminals (the adhesive film for metal terminals before heating in the <tensile modulus A after heating> described later) in a 25°C environment was measured. Specifically, each adhesive film for metal terminals obtained in the examples and comparative examples was cut into a strip with a width (TD) of 15 mm and a length (MD) of 50 mm. Next, for the adhesive film for metal terminals, a stress-strain curve of the test piece was obtained in a 25°C environment using a Tensilon universal material testing machine (RTG-1210 manufactured by A&D Co., Ltd.) under conditions of a tensile speed of 300 mm / min and a chuck distance of 30 mm, and the tensile modulus B of the adhesive film for metal terminals before heating was obtained from the slope of the straight line connecting the two points of strain 0.05% and 0.25%. The results are shown in Table 2.

[0114] <Tensile modulus A after heating> The tensile modulus after heating for 12 seconds at each temperature (140°C, 160°C, or 180°C) shown in Table 2 was measured by the following procedure. First, each adhesive film for metal terminal obtained in the examples and comparative examples was cut into a strip with a width (TD) of 15 mm and a length (MD) of 50 mm. It was placed on a hot plate heated to each temperature, left to stand for 12 seconds, and then immediately left to stand for 1 hour under atmospheric pressure and in a 25°C environment to obtain a test piece. Next, a stress-strain curve of the test piece was obtained under atmospheric pressure and 25°C environment using a Tensilon universal material testing machine (RTG-1210 manufactured by A&D Co., Ltd.) under conditions of a tensile speed of 300 mm / min and a chuck distance of 30 mm, and the tensile modulus A of the adhesive film for metal terminal after heating was obtained from the slope of the straight line connecting the two points of 0.05% and 0.25% strain. The results are shown in Table 2.

[0115] <Measurement of adhesion strength between adhesive film for metal terminals and metal terminals at various temperatures> As the metal terminal, aluminum (JIS H4160:1994 A8079H-O) with a length of 50 mm, width of 22.5 mm, and thickness of 0.2 mm was prepared. Also, each adhesive film for metal terminal obtained in the examples and comparative examples was cut to a width of 15 mm. Next, the adhesive film for metal terminal was placed on the metal terminal to obtain a laminate of metal terminal / adhesive film. Next, a tetrafluoroethylene-ethylene copolymer film (ETFE film, thickness 100 μm) was placed on the laminate and placed on a hot plate heated to 140° C., 160° C., and 180° C., and a 500 g weight with a sponge was placed on it and left to stand for 12 seconds to heat-seal the adhesive film to the metal terminal. The laminate after heat-sealing was naturally cooled to 25° C. Next, in an environment of 25° C., the adhesive film for metal terminal was peeled off from the metal terminal using a Tensilon universal material testing machine (RTG-1210 manufactured by A&D Co., Ltd.). The maximum strength during peeling was taken as the adhesion strength (N / 15 mm) to the metal terminal. The peel speed was 175 mm / min, the peel angle was 180°, and the chuck distance was 30 mm. The average value was taken from three measurements. The results are shown in Table 2.

[0116] [Table 2]

[0117] As described above, the present disclosure provides the inventions of the following aspects. Item 1. An adhesive film for a metal terminal, which is interposed between a metal terminal electrically connected to an electrode of an electricity storage device element and an exterior material for an electricity storage device that encapsulates the electricity storage device element, The adhesive film for a metal terminal has a tensile modulus A value after heating that is smaller than a tensile modulus B value before heating that is described below. Tensile modulus A after heating: the tensile modulus measured in an environment at a temperature of 25°C after leaving the sample to stand for 12 seconds in a heated environment at a temperature of 140°C and then leaving the sample to stand for one hour in an environment at a temperature of 25°C. Tensile modulus B before heating: Tensile modulus measured in an environment at a temperature of 25°C. Item 2. The adhesive film for metal terminal according to item 1, wherein the tensile modulus B before heating is 580 MPa or more. Item 3. An adhesive film for metal terminal according to item 1 or 2, wherein the difference in tensile elastic modulus calculated by subtracting the value of the tensile elastic modulus B before heating from the value of the tensile elastic modulus A after heating is -20 MPa or less. Item 4. The adhesive film for metal terminal according to any one of Items 1 to 3, wherein the tensile modulus A after heating is 580 MPa or more and 700 MPa or less. Item 5. The adhesive film for a metal terminal according to any one of Items 1 to 4, wherein the adhesive film for a metal terminal has a thickness of 140 μm or more. Item 6. The adhesive film for a metal terminal according to any one of Items 1 to 5, wherein the adhesive film for a metal terminal is composed of a laminate having a first polyolefin layer, a substrate, and a second polyolefin layer in this order. Item 7. The adhesive film for metal terminal according to item 6, wherein the resin contained in the substrate contains a polyolefin skeleton. Item 8. The adhesive film for a metal terminal according to item 6 or 7, wherein the first polyolefin layer and the second polyolefin layer contain an acid-modified polyolefin. Item 9. The exterior material for an electricity storage device is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, Item 9. The adhesive film for a metal terminal according to any one of items 1 to 8, wherein the adhesive film for a metal terminal is interposed between the heat-sealable resin layer and the metal terminal. Item 10. A metal terminal with an adhesive film for a metal terminal, comprising the adhesive film for a metal terminal according to any one of items 1 to 9 attached to a metal terminal. Item 11. An electricity storage device including at least an electricity storage device element including a positive electrode, a negative electrode, and an electrolyte, an exterior material for an electricity storage device that seals the electricity storage device element, and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and protrude to the outside of the exterior material for an electricity storage device, 10. An electricity storage device, comprising the adhesive film for a metal terminal according to any one of items 1 to 9 interposed between the metal terminal and the exterior material for an electricity storage device. Item 12. A method for manufacturing a battery including at least an electricity storage device element including a positive electrode, a negative electrode, and an electrolyte, an exterior material for an electricity storage device that seals the electricity storage device element, and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and protrude to the outside of the exterior material for an electricity storage device, A method for producing an electricity storage device, comprising a step of interposing the adhesive film for metal terminal according to any one of items 1 to 9 between the metal terminal and the exterior material for an electricity storage device, and sealing the electricity storage device element with the exterior material for an electricity storage device. [Explanation of symbols]

[0118] 1. Adhesive film for metal terminals 2 metal terminals 3. Exterior materials for energy storage devices 3a Periphery of exterior material for power storage device 4. Energy storage device elements 10. Energy storage devices 11 Base material 12a First polyolefin layer 12b Second polyolefin layer 13 Adhesion promoter layer 31 Base material layer 32 Adhesive layer 33 Barrier Layer 34 Adhesive layer 35 Heat-fusible resin layer

Claims

1. An adhesive film for a metal terminal, which is interposed between a metal terminal electrically connected to an electrode of an electricity storage device element and an exterior material for an electricity storage device that encapsulates the electricity storage device element, The adhesive film for metal terminal is composed of a laminate having a first polyolefin layer, a substrate, and a second polyolefin layer in this order, a ratio of a thickness of the substrate to a total thickness of the first polyolefin layer and the second polyolefin layer is 0.7 or more and 1.5 or less; The adhesive film for a metal terminal has a tensile modulus A value after heating described below that is smaller than a tensile modulus B value before heating described below. Tensile modulus A after heating: the tensile modulus measured in an environment at a temperature of 25° C. after leaving the sample to stand for 12 seconds in a heating environment at a temperature of 140° C. and then leaving the sample to stand for 1 hour in an environment at a temperature of 25° C. Tensile modulus B before heating: Tensile modulus measured in an environment at a temperature of 25°C.

2. The adhesive film for metal terminal according to claim 1 , wherein the tensile modulus B before heating is 580 MPa or more.

3. The adhesive film for metal terminals according to claim 1 or 2, wherein the difference in tensile modulus calculated by subtracting the value of the tensile modulus B before heating from the value of the tensile modulus A after heating is -20 MPa or less.

4. The adhesive film for metal terminal according to any one of claims 1 to 3, wherein the tensile modulus A after heating is 580 MPa or more and 700 MPa or less.

5. The adhesive film for a metal terminal according to any one of claims 1 to 4, wherein the adhesive film for a metal terminal has a thickness of 140 µm or more.

6. The adhesive film for metal terminals according to any one of claims 1 to 5, wherein the adhesive film for metal terminals is composed of a laminate having a first polyolefin layer, a substrate, and a second polyolefin layer in this order.

7. The adhesive film for metal terminal according to claim 6 , wherein the resin contained in the substrate contains a polyolefin skeleton.

8. The adhesive film for a metal terminal according to claim 6 or 7, wherein the first polyolefin layer and the second polyolefin layer contain an acid-modified polyolefin.

9. the electrical storage device packaging material is composed of a laminate having at least a base layer, a barrier layer, and a thermally adhesive resin layer in this order; The adhesive film for metal terminal according to any one of claims 1 to 8, wherein the adhesive film for metal terminal is interposed between the heat-sealable resin layer and the metal terminal.

10. A metal terminal with an adhesive film for a metal terminal, comprising the adhesive film for a metal terminal according to any one of claims 1 to 9 attached to a metal terminal.

11. An electricity storage device comprising at least an electricity storage device element having a positive electrode, a negative electrode, and an electrolyte, an exterior material for an electricity storage device that seals the electricity storage device element, and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and protrude to an outside of the exterior material for an electricity storage device, An electricity storage device, comprising the adhesive film for metal terminal according to any one of claims 1 to 9 interposed between the metal terminal and the exterior material for the electricity storage device.

12. A method for manufacturing a battery including at least an electricity storage device element including a positive electrode, a negative electrode, and an electrolyte, an exterior material for an electricity storage device that seals the electricity storage device element, and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and protrude to an outside of the exterior material for an electricity storage device, A method for manufacturing an electricity storage device, comprising a step of interposing an adhesive film for metal terminal according to any one of claims 1 to 9 between the metal terminal and the exterior material for an electricity storage device, and sealing the electricity storage device element with the exterior material for an electricity storage device.

Citation Information

Patent Citations

  • Sealant for solar battery etc

    JP2005306946A

  • Electric components, nonaqueous electrolyte battery, and lead conductor with insulation coating layer and enclosing container using the same

    JP2007184189A

  • Metal terminal coating resin film for secondary battery

    JP2012022821A

  • Metal terminal-covering resin film for secondary battery use, method for manufacturing the same, and battery pack

    JP2014132538A

  • Terminal with adhesive tape, method of manufacturing terminal with adhesive tape, and thin battery

    JP2015079638A